Lactation Support as a Proxy Measure of Family-Centered Care Quality in Neonates with Life-Limiting Conditions-A Comparative Study - Suneeta Brito; Allison Williams; Jenny Fox; Tazuddin Mohammed; Nayef Chahin; Kaitlin McCarthy; Lamisa Nubayaat; Shirley Nunlist; Mason Brannon; Jie Xu; Karen D. Hendricks-Muñoz (MDPI AG, 2023)
Background: Lactation support is an important measure of Family-Centered Care (FCC) in the Neonatal Intensive Care Unit (NICU). Life-limiting conditions (LLCs) raise complex ethical care issues for providers and parents in the NICU and represent a key and often overlooked population for whom FCC is particularly important. We investigated healthcare disparities in FCC lactation support quality in infants with LLCs. Methods: A retrospective cohort of inborn infants with or without LLCs admitted to the NICU between 2015-2023 included 395 infants with 219 LLC infants and 176 matched non-LLC infants and were compared on LLC supports. Results: The LLC cohort experienced greater skin-to-skin support, but less lactation specialist visits, breast pumps provided, and human milk oral care use. LLC infants also experienced less maternal visitation, use of donor milk (LLC: 15.5%, non-LLC: 33.5%), and breastfeeds (LLC: 24.2%, non-LLC: 43.2%), with lower mean human milk provision (LLC: 36.6%, non-LLC: 67.1%). LLC infants who survived to discharge had similar human milk use as non-LLC infants (LLC: 49.8%, non-LLC: 50.6%). Conclusion: Lactation support was significantly absent for families and infants who presented with LLCs in the NICU, suggesting that policies can be altered to increase lactation support FCC quality for this population.